Analysis of the Application of Justice Principles in Civil Dispute Resolution in Indonesia: A Study of Cases in District Courts - Umar, Nurifana; Sumilat, Rohyani Rigen Is; Ante, Rinny; Paendong, Kristiane Aprilia; Umboh, Joice Jane (Jurnal Smart Hukum (JSH), 2025)
This research analyzes the application of justice principles in the resolution of civil disputes at Indonesian district courts. Employing a qualitative approach, the study examines 15 civil case decisions from five major district courts between 2020 and 2024, complemented by interviews with judges, lawyers, and litigants. The findings reveal that the pursuit of procedural certainty often overrides substantive justice, with strict adherence to procedural rules sometimes resulting in the dismissal of valid claims. Cultural factors, such as the integration of adat (customary law), further complicate the consistency of judicial decisions, particularly in inheritance and land disputes. Additionally, external pressures—including corruption and political influence—pose significant challenges to impartial adjudication. These complexities highlight a persistent tension between legal certainty and fairness in Indonesia’s civil justice system. The study recommends targeted judicial training focused on balancing procedural and substantive justice, enhanced oversight by the Judicial Commission, and reforms to allow greater judicial discretion in procedural matters. By providing an in-depth examination of district court practices, this research contributes to a better understanding of the systemic barriers to achieving justice in Indonesian civil litigation and offers practical recommendations for reform. The findings underscore the importance of aligning legal procedures with the fundamental goal of delivering fair and equitable outcomes for all parties involved.